2023
DOI: 10.3390/ani13020260
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Nutritional Composition, and Digestibility of Conventional and Brown Midrib (BMR) Pearl Millet as Affected by Planting and Harvesting Dates and Interseeded Cowpea

Abstract: The objective of this study was to evaluate the yield, nutritional composition, and digestibility of conventional (CON) and brown midrib (BMR) pearl millet (PM) with different establishment dates, maturity at harvest and when mixed with cowpea (CWP). In trial 1, CON and BMR were planted on two different dates. In trial 2, CON and BMR, mixed or not with CWP, were harvested when PM was at the boot or heading stages. In trial 1, dry matter (DM) yield was similar between both PM genotypes but delaying establishmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
0
5
2
Order By: Relevance
“…Similar to VU DM yield, the PG DM yields measured in this study as monoculture and in mixtures (Table 3) also were considerably greater than those reported by [22] for monoculture FS and FS mixed with legumes (7.38 Mg DM ha −1 ). They were also greater than those measured by Machicek et al [2] for PG harvested 90 DAP and by Oskey et al [18] for a first harvest monoculture PG at early heading. The PG DM yields measured in this study as monoculture and in mixtures (Table 3) were slightly greater than those for monoculture PG reported by others [9,16].…”
Section: Pearl Millet Dm Yield and Nutritive Valuecontrasting
confidence: 48%
See 4 more Smart Citations
“…Similar to VU DM yield, the PG DM yields measured in this study as monoculture and in mixtures (Table 3) also were considerably greater than those reported by [22] for monoculture FS and FS mixed with legumes (7.38 Mg DM ha −1 ). They were also greater than those measured by Machicek et al [2] for PG harvested 90 DAP and by Oskey et al [18] for a first harvest monoculture PG at early heading. The PG DM yields measured in this study as monoculture and in mixtures (Table 3) were slightly greater than those for monoculture PG reported by others [9,16].…”
Section: Pearl Millet Dm Yield and Nutritive Valuecontrasting
confidence: 48%
“…That said, Fontaneli et al [13] reported no difference in CP among SxS and PG cultivars, measuring somewhat greater CP for both forages compared to the PG in the present study (Table 3). Oskey et al [18] reported a negligible influence of PG-VU mixtures on total forage nutritive value other than CP, which generally led to a 10 g kg −1 increase over monoculture PG. They [18] stated that the 10 g kg −1 increase was unlikely to significantly influence animal response.…”
Section: Total Forage Dm Yield and Nutritive Valuementioning
confidence: 99%
See 3 more Smart Citations